Results of Hearing and Vision Tests on Preschool Children at Dharma Wiweka Kindergarten in 2022-2024 - Ni Putu Listya Dewi; Ni Nyoman Budiani; Ni Nyoman Suindri (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2025)
Hearing Test is detect early hearing loss to find abnormalities in hearing. Vision Test is to conduct early detection of vision disorders that result in visual impairment. The purpose of the study was to determine the description of results of vision and hearing tests in preschool children at Dharma Wiweka Kindergarten in 2022-2024. The type of descriptive research is a cross-sectional design using total sampling technique. The study was conducted in March-May 2025 at Dharma Wiweka Kindergarten. The total of samples was 355. Secondary data collection used a data collection checklist. Data analysis is form frequency distribution and percentage. The results of the study showed that the characteristics the respondents were mostly 5 years old (82.3%), proportion of gender was dominated by boys (54.6%). Preschool children showed the results of the vision examination showed that most (92.1%) had normal vision, the results of the hearing examination for most (97.2%) were normal. There are tendency for increase in hearing disorders and vision disorders detected in preschool children Dharma Wiweka Kindergarten from 2022-2024. Routine vision and hearing checks conducted Dharma Wiweka Kindergarten, facilitated by the Denpasar City Health Service, have proven to useful for detecting sensory disorders in children at early stage.